The Purchase Intention for Agricultural Products of Regional Public Brands: Examining the Influences of Awareness, Perceived Quality, and Brand Trust. (26th April 2022) - Sun, Yuling; Huang, Yifan; Fang, Xiang; Yan, Feng
Abstract : Digital economy technologies such as big data, artificial intelligence, and 5G have brought significant changes to the operation and management of regional agricultural products. As a result, competition between agricultural enterprises turned to competition between brands. Recently, many regional brands of agricultural products have emerged, but most have low visibility, low influence, and significant homogeneity. Therefore, ways to rapidly improve public awareness of regional agricultural brands' products have become an important issue in some regions. Against the background of regional brands and on the basis of 576 responses to a survey questionnaire, this study analyzes the direct and indirect influences of awareness and perceived quality on consumers' purchase intention of agricultural products and the mediating influence of brand trust on consumer purchase intention. The results indicate that awareness has a significant positive effect on consumers' purchase intention and that brand trust could strengthen the influence of awareness on consumers' purchase intention. At the same time, brand trust can promote the positive influence of perceived quality on consumers' purchase intention. This study extends the research on consumer behavior theory, reveals the influence mechanism of consumer purchase intention of the agricultural products of regional public brands, and provides a new perspective for further research on agricultural products in some regions. Additionally, we provide management implications for the operation of agricultural products of regional public brands.